Door County citizen survey report, 2009 - Janke, James; Trechter, David; Hadley, Shelly (My University, 2009)
The purpose of this study was to gather opinions of residents about priorities for Door County government.
34 p.
Keywords: Door County (Wis.)--Politics and government; County government--Wisconsin--Door County; Door County, Wisconsin; Door County (Wis.); Door County (Wis.)--Survey; Public opinion--Wisconsin--Door County